Educational and Organizational Handling during COVID-19 Pandemic: Challenges and Changes - Kassy Sey (Journal of General Education and Humanities, 2023)
In light of the current circumstance, this study aimed to look into the difficulties and adjustments educational institutions and organizations underwent during the COVID-19 epidemic. The methodology used in this study was qualitative. Data was collected using Key Informant Interviews (KII) and two focus group discussions. Five participants in the group talks and six in the KII provided the evaluated and analyzed data. Theme-based triangulation and visualization techniques were used to classify and present the collected data. According to the findings, respondents were concerned about how COVID-19's consequences on enterprises, educational institutions, organizations, and individual employee income will affect their ability to operate. Organizations, especially those in educational sectors, have altered work schedules and restrictions, imposed social distancing during the supply of goods and services, and changed workflows. They have also moved away from physical environments and toward virtual supervision and instruction.